PEMANFAATAN CANVA SEBAGAI MEDIA KREATIF UNTUK MENINGKATKAN INOVASI PEMBELAJARAN GURU DI SMA NEGERI 1 POMALAA - Jusnydar.J; Rifka Hafidza Hajar; Ivmal Deprian; Yuspira A.S; Sopia Welmince Nunaki; Junse Rante; Dwi Nabilah Syaharani M; Saleh Sutrisna (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The utilization of digital technology in learning has become an essential requirement in the modern era of education. However, many teachers have yet to optimally utilize technology-based learning media. This community service activity aims to enhance teachers' knowledge and skills in utilizing the Canva application as a creative and innovative learning medium at SMA Negeri 1 Pomalaa. The method used in this activity is a descriptive quantitative approach with a One Group Pretest-Posttest design. The subjects consisted of 15 teachers who participated in training on the use of the Canva application. The activity was carried out through three stages: planning, implementation, and evaluation. In the evaluation stage, measurements were taken via pre-test and post-test to determine the increase in participants' understanding after the training. The results of the activity indicate a significant increase in teachers' understanding of using Canva as a learning medium. The percentage of participants' understanding before the training was 23%, which increased to 92% after the training—a total improvement of 69%, falling into the